A new species of Lessingianthus (Asteraceae: Vernonieae), from Rio Grande do Sul State, Brazil - Deble, Leonardo Paz; Lemos, Rafael Plá Matielo (Balduinia, 2014)
Lessingianthus alegretensis (Asteraceae: Vernonieae) is described and illustrated from sandy grasslands in south west of Rio Grande do Sul State, Brazil. Comments about geographic distribution, conservation and affinities are provided.